EFFICACY EVALUATION OF DIFFERENT DOSES OF TRIAFAMONE IN DIRECT SEED RICE - SHRIKANT CHITALE,; NITISH TIWARI,; VED PRAKASH SAHU, (The Bioscan, 2021)
Experiments was conducted at Indira Gandhi Krishi Vishwavidyalaya, Raipur, during kharif seasons of 2018 and 2019 to find out the efficacy of different doses of triafamone 200 SC in direct seeded rice under irrigated condition. Alternanthera triandra and Echinochloa colona dominated the weed density and composed 92 and 98 % of total weed population respectively during 2018 and 2019. Post emergence application of triafamone 200 SC 100 g/ha at 2 to 3 leaf stage performed best and reduced the weed density very effectively and provided higher weed control efficiency (63.2 and 64.9 %) at 42 DAS over its lower doses and pyrazosulfuron ethyl 10% WP 15 g/ha and cyhalofopbutyl 10% EC 80 g/ha. Triafamone, 200 SC 100 g/ha had produced significantly higher grain yield (4.16 and 4.08 t/ha) of direct seeded rice over pyrazosulfuron ethyl 10% EC 15g/ha and cyhalofop butyl 10% EC 80 g/ha during 2018 and 2019. Triafamone 200 SC 50 g/ha also found to be comparable to that of its highest dose i.e. 100 g/ha. Application of triafamone 200 SC either at 50 or 100 g/ha had no phytotoxic symptom on rice during both the years. PoE of triafamone, 200 SC 100 g/ha and 50 g/ha found to be safe and control weeds effectively.